Internalisasi Nilai Melalui Student Centered Learning (SCL) Approach - Zulfatmi Zulfatmi (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2016)
The learning process that takes place in educational institutions such as schools and even universities are still dry from the effort of planting value for learners. The process that lasted more dominated by the transfer of knowledge (of pouring knowledge) instead of internalizing the values that are important matters in an educational activity. Meanwhile, adult learning methodology has evolved so rapidly, so there has been a learning paradigm shift from teacher-centered learning centered on the learner. As these changes raised concerns some educators to the growing dryness of the learning process of internalization efforts on students in various educational institutions. This study seeks to present a common thread among the various concerns, efforts to internalize the value in educational practice on the one hand and the spirit of the implementation of learning approach centered on the learner on the other side.